P017 Differences in genetic risk for insomnia, hypersomnia and chronotype in bipolar disorder subtypes. (19th November 2019) - Lewis, Katie JS; Richards, Alexander; Karlsson, Robert; Leonenko, Ganna; Jones, Samuel E; Jones, Hannah; Gordon-Smith, Katherine; Forty, Liz; Escott-Price, Valentina; Owen, Michael J; Weedon, Michael N; Jones, Lisa; et al.
Abstract : Introduction: Insomnia, hypersomnia and evening chronotype are common in bipolar disorder (BD) but research examining the role of genetics is mixed. Stratifying by bipolar subtypes could elucidate this relationship and inform sleep and BD research. Aim: to determine whether genetic liability to insomnia, hypersomnia and chronotype differ between bipolar subtypes (type 1, BD-I or type 2, BD-II). Method: Case-control study of 4672 participants with BD (67% female, 3404 BD-I, 1268 BD-II) enrolled in the Bipolar Disorder Research Network and 5714 controls (49% female) recruited from the 1958 British Birth Cohort and UK Blood Service. All participants were of European ancestry. BD subtypes were determined by semi-structured psychiatric interview and case notes. Genetic liability to sleep traits was assessed using genetic risk scores (GRS), which were derived using alleles from genome-wide association studies of insomnia, sleep duration, daytime sleepiness and chronotype. Analyses used multinomial regression to determine whether GRS for insomnia, hypersomnia (daytime sleepiness or sleep duration) and chronotype were associated with BD-I or BD-II when compared to controls. Results: Insomnia GRS were associated with increased risk of BD-II (RR=1.14, 95% CI=1.07–1.21, P=8.26 × 10–5) but not BD-I (RR=0.98, 95% CI=0.94–1.03, P=0.409) relative to controls. Sleep duration GRS were associated with increased relative risk of BD-I (RR=1.10, 95% CI=1.06–1.15, P=1.13 × 10–5), but not BD-II (RR=0.99, 95% CI=0.93–1.06, P=0.818). Daytime sleepiness and chronotype GRS did not distinguish bipolar subtypes. Discussion: Bipolar subtypes differ in genetic liability to insomnia and sleep duration, providing further evidence that bipolar subtypes should be considered separately in research on sleep in BD. The distinct findings for sleep duration and daytime sleepiness support existing literature suggesting that these are distinct subtypes of hypersomnia.